ANALISIS NILAI MORAL DALAM SYAIR NASIB MELAYU KARYA TENAS EFFENDY - Armiansyah, M. Reza; Wahyusari, Ahada; Lolita, Asri; Zaitun; Irawan, Dody; Habiba, Siti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The declining interest of younger generations in Malay literary works has reduced the understanding of the moral values embedded in traditional literature, particularly Syair Nasib Melayu by Tenas Effendy. This study aims to describe the moral values contained in the poem using Subur's theory of moral values. A qualitative approach with a descriptive method was employed. The data source was Syair Nasib Melayu by Tenas Effendy, while the data consisted of poetic stanzas containing moral values. Data were collected through reading and note-taking techniques and analyzed using data reduction, data presentation, and conclusion drawing. The findings revealed 102 data representing 20 categories of moral values, including gratitude, honesty, justice, forgiveness, respect for parents, sincerity, humility, modesty, steadfastness, diligence, self-control, repentance, freedom from greed, generosity, unity, harmony, obedience, patience, responsibility, and time discipline. Among these, diligence was the most dominant moral value with 25 data, followed by generosity and harmony with 10 data each. These findings indicate that Syair Nasib Melayu not only possesses literary and aesthetic value but also serves as a medium for character education based on Malay local wisdom that remains relevant to contemporary society.